Characteristics of Competitive Baton Twirling Athletes - Hatchett, Andrew; Dicks, Alexis; Proctor, Miranda; Trujillo, Amanda (Journal of Sports Research, 2021)
Competitive baton twirling is a sport that combines elements of gymnastics, dance and ballet while necessitating cardiovascular endurance, muscular endurance and power, hand-eye coordination, spatial awareness, kinesthetic awareness, timing and choreography. Approximately one million baton twirlers participating in the sport in the United States. Despite considerable participation in competitive baton twirling, little is known about the characteristics of the athletes. This work documents demographic and behavioral characteristics of competitive baton twirlers. Questionnaires were completed by 169 female twirlers from across the Unites States and Canada. Respondents reported a mean (± SD) age of 18.07 yrs. (±6.08) and height of 63.89 in (±6.24), weight 133.56 lbs. (±32.49), BMI (22.92), GPA 3.73 (±0.31), years of competing 8.02 yrs. (±1.81). All (100%) qualified respondents reported experiencing injury due to competing in or training for baton. The extent of the injuries reported varied greatly. A diversity of training, recovery, hydration, and nutrition habits were also reported. These findings indicate that the competitive baton twirlers that participated in this research are adolescent females, diverse in physical profile, of normal BMI, high academic achievers, dedicated athletes, consistently overcome injuries and train by diverse means. Future research may consider the long-term physical effects and an association with mental health competitive baton twirling has on the athletes.